The Influence Of The Self-Assessment System And Tax Sanctions On Value Added Tax (Vat) Revenue At Kantor Pelayanan Pajak Pratama Binjai - Gaol, Jimmy Hasudungan Lumban; Franita, Riska; Wardhani , Neng Sri (PT. Publikasiku Academic Solution, 2025)
This research aims to analyze the effect of the Self Assessment System and tax sanctions on Value Added Tax (VAT) revenue at Kantor Pelayanan Pajak (KPP) Pratama Binjai. This research is based on the importance of increasing taxpayer compliance in the Indonesian taxation system, which adopts a Self Assessment System, a system in which taxpayers are trusted to calculate, pay, and report their own tax obligations. This research is quantitative in nature with a descriptive and verificative approach. The population in this study was all taxpayers registered at Kantor Pelayanan Pajak (KPP) Pratama Binjai, with a sample size of 136 respondents determined using total sampling technique. Data were obtained through questionnaires and documentation, then analyzed using multiple linear regression with the help of SPSS version 25 software. The partial test results show that the Self Assessment System has a positive and significant effect on VAT revenue with a t-value of 2.778 and a significance of 0.006 < 0.05. This indicates that the better the implementation of the Self Assessment system, the higher the VAT revenue due to increased taxpayer awareness and compliance. Meanwhile, the tax penalty variable also has a positive and significant effect on VAT revenue with a t-value of 8.554 and a significance of 0.000 < 0.05. The implementation of strict penalties encourages taxpayers to be more disciplined in fulfilling their tax obligations. Both variables contribute 37.7% to the increase in VAT revenue.